2013
DOI: 10.1080/09297049.2012.696602
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological profiles of six children with anoxic brain injury

Abstract: Anoxic brain injury (ABI) often results in severe memory impairment and other cognitive and behavioral deficits, although limited information is available regarding pediatric cases. This study reported the neuropsychological outcomes in six children and adolescents who sustained ABI. Profiles were compared by mechanism of injury (ischemic vs. hypoxemic) and three cases were evaluated more than once. Severe intellectual, attention, memory, and behavioral impairments were observed in all six cases although acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Further, parents of children with history of bacterial meningitis reported lower school achievement, higher rates of repeating a year of school, and higher rates of special education referrals six years after infection [ 28 ]. Among a small sample of six children with anoxic brain injury, results show academic impairment, though to a lesser extent than intellectual and memory difficulties, following brain injury [ 114 ]. One study showed that children with a history of anoxic brain injury have poorer academic outcomes than children with a TBI history [ 115 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, parents of children with history of bacterial meningitis reported lower school achievement, higher rates of repeating a year of school, and higher rates of special education referrals six years after infection [ 28 ]. Among a small sample of six children with anoxic brain injury, results show academic impairment, though to a lesser extent than intellectual and memory difficulties, following brain injury [ 114 ]. One study showed that children with a history of anoxic brain injury have poorer academic outcomes than children with a TBI history [ 115 ].…”
Section: Literature Reviewmentioning
confidence: 99%